Persepsi Pendengar Terhadap Program Hiburan Dangdut Di Radio Dapur Remaja 107.8 FM - Ananda Wiliyan; Harmonis Harmonis (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Dangdut music was first born and popularized by Indonesian singers. However, dangdut genres is one that is popular with many people. In the development of music and its various types, it will give rise to various views for each individual towards dangdut music. As a tool used to listen to dangdut music, for example through dangdut music broadcast programs on the radio. To find out listeners' perceptions of the dangdut entertainment program on Dapur Remaja 107.0 FM radio in the acceptance and assessment stages. Robbins' theory of perception and the Qualitative Descriptive method were used for this research to develop the theory found through data from the field. Listeners' perceptions provide views about what they know from the dangdut entertainment program on Dapur Remaja radio is a program containing music broadcasts that entertain listeners and the music played is old dangdut. The perception of listeners who think that listening to music can increase enthusiasm while working, for them listening to dangdut music can increase enthusiasm because dangdut music can be entertainment during activities.